Environmentally and behaviourally mediated co‐occurrence of functional traits in bird communities of tropical forest fragments. Issue 2 (18th September 2017) - Ulrich, Werner; Banks‐Leite, Cristina; De Coster, Greet; Habel, Jan Christian; Matheve, Hans; Newmark, William D.; Tobias, Joseph A.; Lens, Luc
Abstract : Two major theories of community assembly – based on the assumption of 'limiting similarity' or 'habitat filtering', respectively – predict contrasting patterns in the spatial arrangement of functional traits. Previous analyses have made progress in testing these predictions and identifying underlying processes, but have also pointed to theoretical as well as methodological shortcomings. Here we applied a recently developed methodology for spatially explicit analysis of phylogenetic meta‐community structure to study the pattern of co‐occurrence of functional traits in Afrotropical and Neotropical bird species inhabiting forest fragments. Focusing separately on locomotory, dietary, and dispersal traits, we tested whether environmental filtering causes spatial clustering, or competition leads to spatial segregation as predicted by limiting similarity theory. We detected significant segregation of species co‐occurrences in African fragments, but not in the Neotropical ones. Interspecific competition had a higher impact on trait co‐occurrence than filter effects, yet no single functional trait was able to explain the observed degree of spatial segregation among species. Despite high regional variability spanning from spatial segregation to aggregation, we found a consistent tendency for a clustered spatial patterning of functional traits among communities in fragmented landscapes, particularly in non‐territorial species. Overall, we show that behavioural effects, such as territoriality, and environmental effects, such as the area of forest remnants or properties of the landscape matrix in which they are embedded, can strongly affect the pattern of trait co‐occurrence. Our findings suggest that trait‐based analyses of community structure should include behavioural and environmental covariates, and we here provide an appropriate method for linking functional traits, species ecology and environmental conditions to clarify the drivers underlying spatial patterns of species co‐occurrence.